Tolerance in intergroup encounters: Payoffs and plasticity in non-human primates and humans - Pisor, Anne C; Surbeck, Martin (PeerJ Preprints, 2017)
Primate individuals use a variety of strategies in intergroup encounters, from aggression to tolerance; however, despite the prevalence of tolerance in humans, recent focus on the evolution of intergroup contest has come at the cost of characterizing the role of tolerance in human sociality. Can we use the selection pressures hypothesized to favor tolerance in intergroup encounters in the non-great ape primates to explain the prevalence and plasticity of tolerance in humans and our closest living relatives? In the present paper, we review these candidate ecological and social factors and conclude that additional selection pressures are required to explain the prevalence of tolerance in human intergroup encounters; we nominate the need to access non-local resources in the human foraging ecology as a candidate pressure. To better evaluate existing hypotheses, additional, targeted data are needed to document the prevalence and plasticity of tolerance during intergroup encounters in some great ape species.
Keywords: Tolerance; Intergroup encounters; Intergroup contact; Contest competition; Hominoids